Records of Woodiphora Schmitz (Diptera: Phoridae) from animal carcasses in Bangi, Malaysia - Raja Muhammad Zuha Raja Kamal Bashah,; Disney, R. Henry L. (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Four species of Woodiphora Schmitz were collected from rabbit carcasses placed in concealed environments in Bangi, Malaysia. A male Woodiphora distans (Borgmeier) was collected from a rabbit carcass placed inside a luggage case. The other three female Woodiphora were recorded from a rabbit carcass placed inside a water tank and could not be named until linked to their males. This report extends the knowledge of Woodiphora in this region and its association with animal carcasses.